Moving beyond quantity of participation in process evaluation of an intervention to prevent excessive pregnancy weight gain - Paul Keriann H; Olson Christine M (BMC, 2013)
Abstract Background Few lifestyle interventions have successfully prevented excessive gestational weight gain. Understanding the program processes through which successful interventions achieve outcomes is important for the design of effective programs. The objective of this study was to evaluate the effect of the quantity and quality of participation in a healthy lifestyle intervention on risk of excessive gestational weight gain. Findings Pregnant women (N = 179) received five newsletters about weight, nutrition, and exercise plus postcards on which they were asked to set related goals and return to investigators. The quantity of participation (dose) was defined as low for returning few or some vs. high for many postcards (N = 89, 49.7%). Quality of participation was low for setting few vs. high for some or many appropriate goals (N = 92, 51.4%). Fisher's exact tests and multivariate logistic regression were used to analyze the effect of participation variables on the proportion with excessive weight gain. Quantity and quality of participation alone were each not significantly associated with excessive gestational weight gain, while quality of participation among those with high-levels of participation approached significance (p = 0.07). The odds of gaining excessively was decreased when women had both a high quantity and quality of participation (OR = 0.04, 95% CI = 0.005, 0.30). Conclusions Both quantity and quality of participation are important program process measures in evaluations of lifestyle interventions to promote healthy weight gain during pregnancy.